2016
DOI: 10.31578/jebs.v1i1.8
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Project–Based Learning on Undergraduate EFL Students’ Reading Comprehension Ability

Abstract: Globalization in the 21st century and rapid strides in technology have increased the need for communication in English as is has become a lingua franca. English is also needed as a tool to assist academic advancement, career promotion and information-seeking in general. Hence, good English reading comprehension ability and a sufficient vocabulary range are both vital for university students for these purposes. Therefore, educators have to take into consideration these improvements and attempt to apply various … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 11 publications
4
14
0
Order By: Relevance
“…Previous research mostly said that PBL was beneficial for students, such as enhancing their skills in team-working, creativity, and communication skills. Specifically, in the reading class said that PBL could improve their reading comprehension ability (Kavlu, 2015). However, there is still a lack of research perceptions of PBL in Indonesia, especially in the Critical reading class and collected data to determine if PBL has positive impacts on students learning in public colleges.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research mostly said that PBL was beneficial for students, such as enhancing their skills in team-working, creativity, and communication skills. Specifically, in the reading class said that PBL could improve their reading comprehension ability (Kavlu, 2015). However, there is still a lack of research perceptions of PBL in Indonesia, especially in the Critical reading class and collected data to determine if PBL has positive impacts on students learning in public colleges.…”
Section: Discussionmentioning
confidence: 99%
“…This study has a different focus from other previous research, so the findings are also different. For instance, Kavlu (2015) held a detailed study with one experimental and one control EFL learners' groups in Iraq. The study has a focus on reading comprehension, so the effect found from the findings was on the reading comprehension ability only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, Wang (2016) applied PBL to enhance students' motivation using survey. In 2015, Kavlu (2015) found that there was a significant positive improvement in the class using PBL as the teaching method.…”
Section: Introductionmentioning
confidence: 99%
“…PBL offers many opportunities to promote language use and acquisition in real-life contexts because the basic premise of PBL is that learning begins with a problem presented in the same context as it will be encountered in real life (Kumaravadivelu, 2001). According to Ministry of Education and Culture, the benefits of PBL for the students are: (1) increasing their learning motivation and encouraging them to conduct an important work; (2) improving their ability to solve the problem; (3) making them more active and successful in solving complex problems; (4) improving collaboration; (5) encouraging them to develop and practice their communication skill; (6) improving their skill to manage the resources; (7) giving them experiences in learning and organizing the projects, especially in allocating the time and other resources to finish the projects; (8) providing learning experience for living in the real world; (9) activating them to implement their knowledge in the real world; and (10) making learning more interesting so that both students and the teacher enjoy the teaching and learning process.…”
Section: Introductionmentioning
confidence: 99%